The American Journalism Handbook Concepts, Issues, and Skills - Zamith, Rodrigo (Open textbook library., 2022)
This book is designed to help us understand the many changes to U.S. journalism and imagine new futures for it – futures in which it can serve as an even more useful tool for promoting a well-functioning society. But, before we can imagine new futures, we must take a step back and examine the institution of U.S. journalism through a critical and in-depth lens. This book aims to offer just that. It provides a conceptual foundation for understanding the development, logic, and practice of journalism in the United States; describes some of the key challenges, tensions, and opportunities it has faced, is facing, and will likely face; and offers guidance to help individuals develop the skills needed engage in impactful journalism.